2016
DOI: 10.1002/1873-3468.12082
|View full text |Cite
|
Sign up to set email alerts
|

Preferential interaction of the Alzheimer peptide Aβ‐(1–42) with Omega‐3‐containing lipid bilayers: structure and interaction studies

Abstract: Many age-related neurodegenerative diseases, including Alzheimer Disease (AD), are elicited by an interplay of genetic, environmental, and dietary factors. Food rich in Omega-3 phospholipids seems to reduce the AD incidence. To investigate the molecular basis of this beneficial effect, we have investigated by CD and ESR studies the interaction between the Alzheimer peptide Ab-(1-42) and biomimetic lipid bilayers. The inclusion of 1,2-didocosahexaenoyl-sn-glycero-3-phosphocholine does not change significantly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…We first explored by systematically screening the effects of buffer, pH, and ionic strength on the kinetics of glycation and self-assembly to find conditions in which aggregation would be sufficiently slow to follow the glycation process using peptides synthesized in house and previously extensively characterized ( 31 ). Optimal conditions for the reaction were found using 200 m m phosphate buffer at pH 7.4, to have a polar environment in which the Aβ peptides are known to quickly aggregate and adopt a β-conformation ( 32 ). The peptides were always pretreated under strong acidic conditions (TFA) for 1 h and freeze-dried to remove the volatile acid.…”
Section: Resultsmentioning
confidence: 99%
“…We first explored by systematically screening the effects of buffer, pH, and ionic strength on the kinetics of glycation and self-assembly to find conditions in which aggregation would be sufficiently slow to follow the glycation process using peptides synthesized in house and previously extensively characterized ( 31 ). Optimal conditions for the reaction were found using 200 m m phosphate buffer at pH 7.4, to have a polar environment in which the Aβ peptides are known to quickly aggregate and adopt a β-conformation ( 32 ). The peptides were always pretreated under strong acidic conditions (TFA) for 1 h and freeze-dried to remove the volatile acid.…”
Section: Resultsmentioning
confidence: 99%
“…[46] DHA has recently been shown to have this effect. [47] Hence higher membrane levels of EPA and/or DHA may favorably affect the metabolism of Aβ peptides and thereby reduce risk for AD/D progression.…”
Section: Discussionmentioning
confidence: 99%
“…Favourably, they also have a high ratio of n3-PUFA/n6-PUFA of 1:3 to 1:4 (Vinson and Cai 2012;Poulose et al 2014). n3-PUFA are known to reduce the production of peptide amyloid-beta (Aβ) (Emendato et al 2016;Thomas et al 2015), commonly associated with AD, and additionally improve health of brain cells (Carey et al 2013). For example, in accordance with Cole et al we reported that DHA improved the fluidity of neuronal membranes (Cole et al 2009;Eckert et al 2011).…”
Section: Introductionmentioning
confidence: 70%